Teaching Statistics to Struggling Students: Lessons Learned from Students with LD, ADHD, and Autism - Dahlstrom-Hakki, Ibrahim; Wallace, Michelle L. (Journal of Statistics and Data Science Education, 2022)
There have been significant developments in the field of statistics education over the past decade that have improved outcomes for all students. However, there remains relatively little research on the best practices for teaching statistics to students with disabilities. This article describes a conceptual visual approach to teaching a college level general education statistics course aimed at addressing the needs of students with disabilities and other struggling students. The conceptual visual components were employed using the technology tool TinkerPlots. The approach is informed by the recommendations of the GAISE report as well as research on Universal Design and Cognitive Load Theory. With support from the NSF (HRD-1128948), the approach was pilot tested at a college that exclusively serves students with LD, ADHD, and autism to gather preliminary evidence of its effectiveness in teaching statistics concepts to that population. The results of this research and the emergent recommendations to help students with disabilities gain access to statistics are described in this article. Supplementary materials for this article are available online.